DATA MINING AND KNOWLEDGE DISCOVERY - Valcárcel Asencios, Violeta (2004)
The present article emphasizes the use of data mining for the discovery of knowledge, with the purpose of contributing in taking tactical decisions and strategies within an organization providing an automated sense to generate knowledge. Techniques, the predictive power of statistical models and the contribution of the various fields of the research have been included.